(untitled) (Research, Society and Development, 2021)
The aim of this study was to investigate the production of anti-Listeria bacteriocins by naturally occurring bacteria on silage and to characterize the most promising bacteriocin. The production of bacteriocins was evaluated by the spot-on-lawn method. The presence of interfering factors and the sensitivity to proteinase K were analyzed. The spectrum of activity was determined and the most promising bacteriocin-producing isolate was identified, being selected for the subsequent experiments. The antimicrobial peptide was extracted, analyzed regarding temperature and pH sensitivities, and purified. Of the 37 isolates evaluated, seven showed anti-Listeria activity. The presence of bacteriophages and production of acidic compounds were not detected. The selected antimicrobial compound was sensitive to proteinase K and the producing-bacterium was identified as Bacillus velezensis. The crude extract maintained the antimicrobial activity in different temperatures and pH conditions. In conclusion, the bacteriocin produced by Bacillus velezensis showed strong activity against Listeria monocytogenes, and great stability to elevated temperature and adverse pH, desirable features for future biotechnological applications.